Effects of Social Media on Nursing Students in Private University - Kijsomporn, Jureerat; Punkla, Sujintana; Paupairoj, Voranich; Wan Niu, Voon Betty; Ramalingam, Vinodhkumar; Wong, Ling Shing (Journal of Health Science of Thailand, 2025)
Social media has become an integral part of university students’ daily lives, impacting their education, social interactions, and overall well-being. This descriptive research examines the effects of social media usage among first-year nursing students at a private university in Thailand, focusing on physical, mental, and social aspects. The study involved 121 participants, primarily female, aged between 18–20 years. Data was collected through questionnaires covering demographics, the effects of social media, and strategies for reducing its negative impact. The reliability of the questionnaire was verified using Cronbach’s alpha coefficient, yielding a score of 0.80, confirming its validity. The results indicate that while social media facilitates learning and networking, excessive use contributes to adverse effects such as headaches, decreased concentration, and social media addiction. To mitigate these negative impacts, students suggested strategies such as engaging in offline activities, limiting screen time, reducing online shopping, and increasing the use of libraries for academic purposes. This study emphasizes the importance of balanced social media usage to maximize benefits while minimizing negative consequences. Recommendations include developing digital literacy programs and fostering collaboration between universities and parents to promote responsible social media use among nursing students.